A simple and precise LC-MS/MS method for the simultaneous determination of serum 25-hydroxyvitamin D3 and D2 without interference from the C3 epimer. Issue 12 (21st June 2015) - Wang, Siming; Wang, Shu; Yang, Ruiyue; Zhou, Weiyan; Li, Hongxia; Dong, Jun; Chen, Wenxiang
<x xml:space="preserve">Abstract</x> The protocol provides a simple and precise determination of serum 25-hydroxyvitamins D3 and D2 without interference from the C3 epimer, which can be applied to the clinical measurement and research.